Productive and reproductive performance of Holstein cows subjected to lacto-induction - García B., Cristina (2020)
The aim of this study was to evaluate the productive and reproductive performance of cows submitted to an induced lactation protocol in a commercial dairy farm in Lima, Perú between 2015 and 2017. A total of 98 records of complete induced lactation and 191 records of normal lactations, both primiparous and multiparous were studied. Total production, corrected production and lactation length, as well as the conception rate and the number of services per conception were evaluated. The average total and corrected milk production were 7546 and 6641 kg, respectively, and 367 days of lactation length for induced lactation cows, while for normal lactating cows, values of 10129.8 kg, 8432.1 kg and 408.9 days were obtained, respectively (p<0.05). Likewise, induced lactation cows obtained 58% of pregnancy with 3.9 services/conception compared to control cows with 72.3% (p<0.05) and 3.6 services/conception. Animals subjected to the induced lactation protocol achieved lactations up to 80% of the productions achieved by cows with natural lactations.